2015
DOI: 10.1128/ec.00153-14
|View full text |Cite
|
Sign up to set email alerts
|

Asexual Propagation of a Virulent Clone Complex in a Human and Feline Outbreak of Sporotrichosis

Abstract: Sporotrichosis is one of the most frequent subcutaneous fungal infections in humans and animals caused by members of the plant-associated, dimorphic genus Sporothrix. Three of the four medically important Sporothrix species found in Brazil have been considered asexual as no sexual stage has ever been reported in Sporothrix schenckii, Sporothrix brasiliensis, or Sporothrix globosa. We have identified the mating type (MAT) loci in the S. schenckii (strain 1099-18/ATCC MYA-4821) and S. brasiliensis (strain 5110/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 67 publications
6
52
0
Order By: Relevance
“…Thus, cats remain the main source of infection of S. brasiliensis in South and Southeast Brazil. 1,3,12,18,30 It is remarkable that close related Sporothrix, i.e. S. schenckii s. str.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Thus, cats remain the main source of infection of S. brasiliensis in South and Southeast Brazil. 1,3,12,18,30 It is remarkable that close related Sporothrix, i.e. S. schenckii s. str.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the high number of cases in a short period is compatible with the ongoing situation reported earlier in other endemic areas of Brazil. [1][2][3]6,12,14,15,19,20,28,29 The real prevalence of feline sporotrichosis is likely to be underestimated in Southern Brazil, since it is not an obligatorily reported disease. We considered only the cases referred to FAMED-FURG and with confirmed laboratorial diagnosis of sporotrichosis, i.e., by isolation of Sporothrix in culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors also consider an intron present in a conserved position within the MATα1 domain ( Figure 3) as characteristic of the MAT1-1-1 gene (Kanematsu et al, 2007;Waalwijk et al, 2002;Wilken et al, 2014), although this intron might not be universally present (e.g. the human pathogen Sporothrix schenckii; Teixeira et al, 2015).…”
Section: Genes Encoded On the Mat1-1 Idiomorphmentioning
confidence: 99%
“…Furthermore, recent studies of fungal collections have demonstrated the presence of S. mexicana and S. globosa in clinical samples obtained from patients since 1955 . S. brasiliensis was reported in Brazilian mammalian outbreaks over the last few decades, highlighted by the contamination of semi‐domestic felines ( Felis catus ) with transmission to humans . In Mexico, sporadic infection by cats has been documented, even though S. brasiliensis has not been reported in this country.…”
Section: Introductionmentioning
confidence: 99%